Abdominal epilepsy- A diagnosis often missed! - A case report - Dr. Shivani Deswal; Dr. Paramita Paul; Dr. Murugan S.; Dr. T.P. Yadav (Pediatric Review: International Journal of Pediatric Research, 2018)
Abdominal Epilepsy is a rare cause of recurrent abdominal pain in children. Paroxysmal episodes of pain abdomen with neurological symptoms like dizziness, post-ictal sleep or lethargy, specific electro-encephalographic changes and improvement in symptoms after treatment with antiepileptic drugs help in diagnosis of abdominal epilepsy. We report a seven-year-old girl with recurrent episodes of abdominal pain. Cause of pain remained undiagnosed despite extensive investigative workup. Meticulous history and pain diary gave clue to the diagnosis. EEG conducted during pain episode was abnormal. Treatment with Valproate resolved the pain. Normalization of EEG findings on follow up confirmed the diagnosis of abdominal epilepsy.